Comparative diagnostic efficacy of microscopy, combined flotation and polymerase chain reaction to detect Giardia spp. in dogs and cats - O. P. Kurnosova; V. S. Zaitsev; M. V. Arisov (Российский паразитологический журнал)
The purpose of the research is to perform a comparative diagnostic efficacy of microscopy, combined flotation method and polymerase chain reaction (PCR) used to detect Giardia spp. in dogs and cats.Materials and methods. The efficacy was compared between three methods to detect Giardia spp. on 60 fecal samples from dogs and cats from the Zaitsev+ and Paster Veterinary Laboratory.Results and discussion. The highest diagnostic efficacy was established for PCR, 78.3%; the diagnostic efficacy of combined flotation was 68.3%; the lowest diagnostic efficacy was found for the microscopy method, 43.3%. The combined flotation method to detect Giardia spp. is widely used in laboratory practice as it allows detection of other intestinal parasites in addition to Giardia spp. Microscopy is the fastest and simplest method for detecting not only Giardia spp. but also other intestinal parasites.